Survey Analysis: Enhancing the Security of Vectorization by Using word2vec and CryptDB - Hana Yousuf; Said Salloum (Advances in Science, Technology and Engineering Systems Journal, 2020)
Vectorization is extracting data from strings through Natural Language Processing by using different approaches; one of the best approaches used in vectorization is word2vec. To make the vectorized data secure, we must apply a security method, which will be CryptDB. The paper is analyzing the survey, which is created to interview security engineers through the SPSS tool. By analyzing the responses from software security engineers, it is seen that both word2vec and CryptDB works significantly. Word2vec is an effective vectorization approach, while CryptDB is an effective, secure database. In future work, we will be developing a secure vectorization using both approaches
Keywords: Natural Language Processing Vectorisation; Word2vec; CryptDB